Connectivity and Order: an Analytical Framework - Gaens Bart; Sinkkonen Ville; Vogt Henri (Springer Nature, 2025)
IR literature has become inundated with different descriptions for the future of international order. The coming age is purportedly marked by China’s ascendancy, American decline, a leaderless “no-one’s world”, or multiple competing modernities. Yet the global fight against climate change or shared COVID-19 strategies convey a different image of the world’s predicament. The situation appears paradoxical: increasingly tense great-power relations are mixed with ever-strengthening interdependencies. This article contributes to these debates by exploring how global orders as well as regionalism today are increasingly defined by various types of connective functional links between intentional actors at various levels of social organisation. To enable a nuanced analysis, the article introduces an analytical framework composed of six connectivity logics, namely cooperation, copying, cushioning, contestation, containment, and coercion. These play out differently within material, economic, institutional, knowledge, people-to-people, and security spheres. The utility of this article’s approach is demonstrated through empirical examples related to the policies of key actors in the Indo-Pacific region.